Attitudes and behavior toward human rights across different contexts: the role of right-wing authoritarianism, political ideology and religiosity - Moghaddam, F M; Vuksanovic, V (International journal of psychology, 1990)
Reasoned that Canadian subjects would be more critical of the human rights records of Soviet and the Third World societies, and thus show stronger support for human rights in these than in Canadian society. Predicted that right-wing political ideology and support for human rights would be negatively correlated in contexts Canada and Third World, but not in the Soviet context; and the same pattern between religiosity and support for human rights. Authoritarians, because of their fundamental opposition to individual liberties, would oppose human rights in all contexts. (Abstract amended)